Pemanfaatan Rest Api Sebagai Arsitektur Komunikasi Untuk Peningkatan Unjuk Kerja Sistem Informasi Sekolah Terpadu - Muhamad Ilham, Lukman; Hermanto, Agus (Universitas Darussalam Gontor, 2024)
Abstrak Sistem informasi telah dimanfaatkan dalam berbagai sektor, salah satunya yaitu sektor pendidikan. SDIT BISA Jakarta Barat merupakan salah satu lembaga pendidikan yang memanfaatkan sistem informasi dalam bentuk website. Peneliti merasa bahwa sistem informasi dalam bentuk website masih bisa ditingkatkan unjuk kerjanya. Dalam upaya meningkatkan unjuk kerjanya, peneliti mengembangkan sistem informasi tersebut ke dalam bentuk aplikasi Android dengan memanfaatkan REST API sebagai arsitektur komunikasi antara aplikasi dengan server. Penelitian ini meneliti 3 aspek yaitu b Kata kunci: Android, REST API, Sistem Informasi Abstract [Utilization of REST API as Communication Architecture for Performance Improvement of Integrated School Information System] Information systems have been used in various sectors, one of which is the education sector. SDIT BISA West Jakarta is one of the educational institutions that uses information systems through websites. Researchers feel that the performance of information systems in the form of a website can still be improved. To improve its performance, researchers developed the information system into an Android application by utilizing the REST API as a communication architecture between the application and the server. This research examines 3 aspects, namely how to develop an Android-based Integrated School Information System using the REST API, how to implement an Android-based Integrated School Information System using the REST API, and how to improve the performance of the Integrated School Information System using the REST API. The stages of this research are application development, indicator search, indicator testing, and evaluation of test results. This research uses 10 indicators, namely Usability, Functionality, Reliability, Portability, Integrity, Supportability, Correctness, Maintainability, Interoperability, and Efficiency. The results showed that 6 indicators (Usability, Functionality, Portability, Supportability, Correctness, and Maintainability) have increased, 2 indicators (Integrity and Interoperability) have not changed, and 2 (Reliability and Efficiency) indicators have decreased. Keywords: Android, Information System, REST API